Indonesian Islamic Bank Financing in Increasing Halal-Based Micro, Small and Medium Enterprises in the Industrial Era 5.0‎ - Siregar, Fitri Ana; Siregar, Erwin Saputra (IAIN Kudus, 2024)
Micro, Small and Medium Enterprises Financing is financing provided by business-based Islamic financial institutions, meaning that the capital is rolled out for working capital. Increased public awareness of halal matter and strong stakeholder support are important factors in the development of the halal industry ecosystem in Indonesia. The Industrial Era 5.0 had an impact on all existing sectors including the economic sector in the form of banking and halal-based business entities. This study discusses Indonesian Islamic Banks in halal-based Micro, Small and Medium Enterprises financing in the industrial era 5.0 which has an impact on the economy in Indonesia. It is based on literature research in the form of reading financial archives, field observations, and analysis results from the financial statements of Bank Syariah Indonesia. This study argues that financing Bank Syariah Indonesia as a provider of capital will increase Halal-based Micro, Small and Medium Enterprises supported by the use of digital media in the era of industrial 5.0.